Laboratory Testing of Embankment on Soft Soil by Shaking Table - Ripon Hore; Sudipta Chakraborty; Mehedi A. Ansary (European Science Publishing, 2023)
This paper presents the results of shaking table tests on geotextile-reinforced embankment lying on soft clay. Construction of model embankment in a laminar box mounted on a shaking table, instrumentation and results from the shaking table tests have been discussed in detail. The base motion parameters have been varied in different model tests. It is observed from these tests that the response of the embankment with soft clay has been significantly affected by the base acceleration levels, frequency of shaking and magnitude of surcharge pressure on the crest. The effects of these different parameters on acceleration response at different elevations of the embankment, pore pressures and face deformations have also been presented. The results obtained from this study are helpful in understanding the relative performance of reinforced soil-embankment under different test conditions used in the experiments.
Keywords: Shaking table, Laminar box, Soft soil, Amplification